Uncertainty in monetary cost estimates for assessing working postures using inclinometry, observation or self-report - Waleh Åström, A.; Heiden, M.; Mathiassen, Svend; Strömberg, A. (Elsevier, 2018)
© 2018 Objective: To assess uncertainty in cost estimates for collecting posture data by inclinometry, observations and self-report. Method: In a study addressing physical workloads at a paper mill, costs were calculated for measuring postures of twenty-eight workers during three shifts. Uncertainty in costs was assessed for all three methods as the range between an assumed best case (lowest cost) and worst case (highest cost) using scenario analysis. Results: The cost for observation was larger, but also more uncertain (€16506 and €89552 in the best and worst case, respectively) than that of inclinometry (€7613 - €45896). Self-report costs were both lower and less uncertain (€3743 - €23368). Conclusions: The extent of uncertainty in cost estimates implies that observation could be less expensive than inclinometry, e.g., in a scenario where experienced observers could use existing software, while inclinometers would have to be purchased. We propose adding uncertainty assessments to cost estimates when selecting a method for measuring working postures, and offer guidance in how to proceed in a specific setting.